What Are They Talking About? Lessons Learned from a Study of Peer Instruction - Federica Barbieri (Astronomy Education Review, 2008)
The goal of this study was to investigate the impact of high-stakes grading incentive (specifically, which assigns little credit for incorrect CRS responses) on the interaction produced by students during Peer Instruction (Mazur, 1991) using Classroom Response Systems (CRSs). The study was based on a random sample of transcribed recordings collected from three large section introductory courses in Astronomy taught by two professors, over two semesters at a medium-size US university. The interaction produced by the students was examined through content analysis (using Kartinen and Kampulainen’s (2002) taxonomy) and through discourse bias. Discourse bias was operationalized as amount of talk and calculated using complex corpus linguistic techniques of analysis. Findings suggest that when instructors adopt a high-stakes grading incentive that assigns little credit for incorrect CRS responses rather than providing forums for the spontaneous exploration of nascent ideas, conversations tend to become dominated by a single partner as students attempt to earn maximum credit for a correct answer. The contribution of the study lies in the finding that grade incentive affects the kind of interaction taking place in Peer Instruction, and in the fact that corpus linguistics methods of discourse analysis can be fruitfully applied to educational studies of classroom interaction.